Evaluation of 3G Network Availability Based on Key Performance Indicators in Makassar City - Razak, Irawati; Bazaergan, Abdullah; Palinggi, Sandryones (International Conference on Multidisciplinary Research, 2020)
BTS functions as an interconnection between the cellular system infrastructure and the Out Station. BTS must always monitor station exits that enter and leave the BTS cell. Ideally, one cell will be served by one BTS site. Topographic quality of BTS refers to the Key Performance Indicators (KPI). The parameters used are Availability, Call Drop Rate-Circuit Switch (CDR CS), Call Drop Rate-Packet Switching (CDR PS), Call Setup Success Rate-Circuit Switching (CSSR CS) and Call Setup Success Rate-Packet Switching (CSSR PS). The purpose of this research is to analyze the facts of cellular networks, especially 3G networks in Makassar City based on the standards set by the International Telecommunication Union (ITU). The results obtained from this study are the proportion of the KPI parameters. For the availability parameters, the best value obtained is 30. For the CDR CS parameter, the best value is 0.2436. For the CS CSSR parameter, the best value is 30. Whilst, for the CDR PS parameter, the best value is 0.0517. Whereas for the CSSR PS parameter, the best value is between 29.9515 to 29.9811.Â Keywords: evaluation, 3G, cellular, key performance indicators, mobile network operators